Ideologi wacana korupsi dalam pemberitaan kasus korupsi PT Timah pada portal berita Tempo.co - Nurrohmah, Anisa; Setiawati, Eti (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This study aimed to uncover the ideology of corruption discourse in reporting the PT Timah corruption case on Tempo.co news portal. The method employed was descriptive qualitative with Norman Fairclough's approach, encompassing three dimensions: (1) the text dimension, analyzed using descriptive techniques to identify vocabulary, phrases, and grammar; (2) the discourse practice dimension, analyzed through interpretation techniques covering text production and consumption; and (3) the sociocultural dimension, analyzed using explanatory techniques to link the interpretation results with situational, institutional, and social contexts. The findings revealed that the text dimension contains ideological vocabulary and phrases such as crime, raid, corruption, obstruction of justice, and phrases like adding up to 16 suspects, harming the state, environmental losses, and fantastic losses. In discourse practice, Tempo.co's reporting reflected anti-corruption ideology, transparency, and accountability, with public responses characterized by anger, disappointment, and sarcasm. In the sociocultural dimension, the news was written when corruption became a public concern. Institutionally, it represented Tempo.co's response to the case, while socially, it highlighted the impact of corruption on Bangka Belitung's economy, environment, and society. This study contributes to critical discourse analysis focusing on representing anti-corruption ideology more transparently and accountable in Indonesia.